Binational Analysis of Maternal Mortality Between Brazil and Portugal in 2020–2023: A Population-Based Epidemiological Study. - Gonçalves dos Santos, Gustavo; Silva, Mónica Alexandra Pinho da; Guerra, Maria João Jacinto; das Neves Carvalho, Júlia Maria; da Fonseca Dias, Ana Cristina Ribeiro; Bettencourt, Maria Luísa Santos; Oliveira, Cely de; Feichas Renó, Bruna; Tramontina Cerqueira, Eneida; Rocha de Almeida Farias, Katucha (Nursing Reports, 2026)
Background/Objectives: Maternal mortality remains an important indicator of health inequities, reflecting social, regional, and racial inequalities, as well as the responsiveness of health systems. This study aimed to analyze and compare maternal mortality between Brazil and Portugal from 2020 to 2023. Methods: This is a binational ecological and observational study based on secondary data from official records of live births and maternal deaths in both countries. Maternal mortality rates were calculated per 100,000 live births and stratified by sociodemographic and regional variables. Poisson regression models offset by the logarithm of live births were used to estimate adjusted incidence ratios (IRR) and 95% confidence intervals. Analyses were conducted using R and Stata software. Results: Brazil presented rates between 55 and 62 per 100,000 live births, while Portugal maintained lower values, ranging from 8 to 20 per 100,000. In Brazil, higher risks were observed among Black and Indigenous women, residents of the North and Northeast regions, and in age groups above 30 years. Direct and indirect causes showed similar proportions, with an increase in indirect causes during the pandemic. In Portugal, mortality showed low magnitude, but annual fluctuation was attributed to the small number of events and the limitation of microdata. Conclusions: The study highlights strong structural and racial inequalities in Brazilian maternal mortality, contrasting with the lower magnitude and greater stability observed in Portugal. This reinforces the need for intersectoral actions, strengthening the obstetric network, and continuous surveillance to reduce preventable deaths and promote equity in maternal care.